Improving performance of recently introduced flow cytometry‐based approach of malignant cell screening in serous cavity effusion. (23rd June 2020) - Sun, Jingfang; Ding, Shuang; Zhu, Liqiang; Liu, Yun; Jiang, Qingqing; Song, Shuang; Chen, Weimin; Li, Shibao; Ma, Ping
Abstract: Introduction: Microscopy has been recognized as the "gold‐standard" cellular analysis of serous cavity effusion. However, this method is time‐consuming, labor‐intensive, and requires accomplished skills. Here, we investigated the efficiency of hematology analyzer in screening malignant cells in serous cavity effusion. Methods: A total of 991 serous cavity effusion samples and 370 validation specimens collected from different departments were sent to the clinical laboratory for routine cell count using the automated hematology body fluid (BF) mode and exfoliative cytology simultaneously. High‐fluorescent cells (HFCs) were measured as the relative count (HF%) and absolute count (HF#) by BF mode. Receiver operating characteristic curve analysis was combined with scattergram rules to screen malignant cells. Results: HF# and HF% in malignant samples (subgroup) were significantly higher than those in benign samples, and the HF# and HF% levels were different between ascites and pleural effusion (PE). The area under the curve values were also different between ascites and PE. Positive of malignant cells was very high when the ascites or PE sample touching Rule 1 positive and either Rule 2 negative or positive. The cutoff levels of HF# were 5.5 HFC/μL on the basis of Rules 1 and 2 negative, whereas 83.5 HFC/μL on the basis of Rule 1 negative but Rule 2 positive in ascites. By contrast, the cutoff levels of HF% were 0.55 HFC/100 WBC on the basis of Rules 1 and 2 negative, whereas 4.95 HFC/100 WBC on the basis of Rule 1 negative but Rule 2 positive in PE. Conclusions: Serous cavity effusion will be increasingly analyzed using the automated hematology analyzer BF mode in the future because of its rapidness and convenience. The combined application of HFC with scattergram rules is a feasible and useful approach to screen malignant cells in serous cavity effusion.